Antimicrobial, anticancer, and biofilm inhibition studies of highly reduced graphene oxide (HRG): In vitro and in silico analysis - Alangari, Abdulaziz; Mateen, Ayesha; Alqahtani, Mohammed S.; Shahid, Mudassar; Syed, Rabbani; Shaik, Mohammed Rafi; Khan, Mujeeb; Adil, Syed Farooq; Kuniyil, Mufsir (Frontiers in Bioengineering and Biotechnology, 2023)
Background-Bacterial infections and cancers may cause various acute or chronic diseases which have become serious global health issues. This requires suitable alternatives involving novel and efficient materials to replace ineffective existing therapies. In this regard, graphene composites are being continuously explored for a variety of purposes including biomedical applications, due to their remarkable properties. Methods-Herein, we have explored in-vitro different biological properties of highly reduced graphene oxide (HRG) including anti-cancer, anti-bacterial, and anti-biofilm properties. Besides, to analyze the interactions of graphene with proteins of microbes, in silico docking analysis has also been carried out. To do this, HRG was prepared by using graphene oxide as precursor, which is further reduced by a chemical method to obtain the final product. The as-prepared HRG was characterized by using different types of microscopic and spectroscopic techniques. Results-The HRG revealed significant cytotoxic ability in a dose-dependent anti-cell proliferation approach which substantially killed human breast cancer cells (MCF-7) with IC50 of 29.51±2.68 μg/mL. The HRG demonstrated efficient biological properties i.e., even at low concentration, HRG has exhibited efficient anti-microbial properties against a variety of microorganisms. Among different strains, Gram-positive bacteria such as B.subtilis, MRSA and S. aureus are relatively more sensitive to HRG when compared to Gram-negative bacteria. The bactericidal properties of HRG is almost similar to a commercially available effective antibiotic (ampicillin). To evaluate the efficacy of HRG against bacterial biofilms, P. aeruginosa and MRSA were applied, and the results were compared with gentamycin and ampicillin, which are commonly, applied standard antibiotics. Notably, HRG demonstrated high inhibition (94.23%) against P.aeruginosa, with lower MIC (50 µg/mL) and IC50 (26.53 µg/mL) values, whereas, the ampicillin and gentamicin have shown similar inhibition (90.45% and 91.31%. respectively), but at much higher MIC and IC50 values. Conclusion-Therefore, these results reveal the excellent biopotential of HRG in different biomedical applications, including cancer therapy, antimicrobial activity especially anti-biofilm activity and other biomedicine based therapies. Based on the molecular docking results of Binding energy, it has been predicted that pelB protein and HRG formed the best stable docking complex, and revealed high hydrogen and hydrophobic interactions between the pelB protein and HRG.